Crafting an 'authentic' monster: Dialogue, genre and ethical questions in Mindhunter (2017). (1st June 2019) - Moulton, Erica
Extended scenes of idiosyncratic dialogue between a serial killer and profiler are emblematic of the first season of Joe Penhall and David Fincher's Netflix series Mindhunter. In examining this aspect of the series, my article engages with several burgeoning areas of study in screenwriting and adaptation, notably the intersection of ethics, genre and dialogue. Mindhunter falls squarely into the serial killer subset of the crime procedural genre, following two FBI agents as they interview incarcerated killers under the purview of the newly formed Behavioral Science Unit. In exploring the origin and deployment of highly psychologized speech, I argue that conventions within the serial killer subgenre and the invocation of non-fictional source material led the show's writers to rely on codes of 'authenticity' in crafting the dialogue. Building on studies of screenwriting and genre by Jule Selbo, I also argue that the interview scenes depicted on Mindhunter between the FBI agents and the serial killers can be broken down into various dialogue typologies. The dialogue in these scenes presents the killer as a fount of wisdom, the investigator as an eager receptacle and the psychological boundaries between the two characters as disturbingly permeable. I conclude by probing the ethical underpinnings of this typology considering how screenwriters navigate the tensions between on-screen representation and the framing of 'authentic' content.